2018
DOI: 10.1038/s41419-018-1058-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide, an antiprotozoal drug, inhibits late-stage autophagy and promotes ING1-induced cell cycle arrest in glioblastoma

Abstract: Glioblastoma is the most common and aggressive primary brain tumor in adults. New drug design and development is still a major challenge for glioma treatment. Increasing evidence has shown that nitazoxanide, an antiprotozoal drug, has a novel antitumor role in various tumors and exhibits multiple molecular functions, especially autophagic regulation. However, whether nitazoxanide-associated autophagy has an antineoplastic effect in glioma remains unclear. Here, we aimed to explore the underlying molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 45 publications
4
28
1
Order By: Relevance
“…We ଏnd that both thiazolides arrest CRC cells in the G1 phase of the cell cycle, independent of their ability to cause cell death. Although NTZ has been recently shown to induce autophagy-related cell cycle arrest in glioblastoma cell lines [28], we here demonstrate that in CRC cells thiazolideinduced G1 arrest is primarily regulated by the mTOR/c-Myc/p27 axis. Our study also revealed differences and similarities between these two compounds.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We ଏnd that both thiazolides arrest CRC cells in the G1 phase of the cell cycle, independent of their ability to cause cell death. Although NTZ has been recently shown to induce autophagy-related cell cycle arrest in glioblastoma cell lines [28], we here demonstrate that in CRC cells thiazolideinduced G1 arrest is primarily regulated by the mTOR/c-Myc/p27 axis. Our study also revealed differences and similarities between these two compounds.…”
Section: Discussioncontrasting
confidence: 60%
“…Subsequently, various high-throughput screenings conଏrmed the anticancer activity of NTZ in 2D and 3D culture systems of tumor cells. While activities of NTZ on a broad range of cellular pathways, e.g., metabolism, proliferation, and autophagy, have been reported, no clear mechanism of antitumor activity has been described so far [28][29][30][31]. Thus, further investigations are required to shed light on the antitumor activity of NTZ to fully exploit its anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, chloroquine, apart from disorganizing the Golgi, induces lysosomal alkalinization, which prevents amphisome/autophagosome-lysosome fusion and blocks the vesicle trafficking system [ 53 , 54 , 55 , 93 ], which potentially affects the replication cycle of coronavirus systemically, including their entry, which is mediated by pH-dependent endocytosis and requires a low pH for the S protein to trigger its membrane fusion activity [ 94 , 95 ]. Nitazoxanide is another late-stage autophagy blocker [ 96 ] that shows high anti-SARS-CoV-2 activity in cell cultures (IC 50 : 2.12 μM) [ 97 ], although it should be considered that its main metabolite, tizoxanide, induces autophagy by inhibiting the PI3K-AKT-MTOR pathway [ 98 ]. At this moment, the scientific community is focusing efforts in searching, by different approaches, for effective drugs against this pathogen and continuously revealing autophagy modulators [ 99 , 100 , 101 ].…”
Section: Autophagy Modulators Are Promising Anticoronaviralsmentioning
confidence: 99%
“…Several analgesics and anesthetics, and antipsychotic, antibiotic and antiprotozoal drugs, among many other classes, have already been repurposed or are being tested on an oncology setting, based on modulation of numerous cell signaling pathways commonly disrupted in cancer [185]. Nitazoxanide (NTZ) is an antiprotozoal drug, which has been recently shown to inhibit autophagy in glioblastoma cells [187]. The combination with chloroquine (CQ), a well-known antimalarial autophagy inhibitor, had a synergistic effect, with CQ sensitizing the glioma cells to NTZ.…”
Section: Drug Repurposingmentioning
confidence: 99%